Clustering value-added trade: Structural and policy dimensions - Hubert Escaith; Hadrien Gaudin (World Trade Organization (WTO), 2014)
A second approach focuses on the relationships existing between the variables themselves, using multi-criteria and graph analysis. Natural resources endowments, on the one hand, and services orientation, on the other one, are among the most determinant variables for defining Trade in Value Added (TiVA) clusters. The level of economic development remains a crucial determinant of the TiVA profile as is the size of the economy, even if not as important as initially expected. Pro-active GVC up-grading strategies, such as investments in ICT and R&D tend to foster a higher foreign content in exports, compensating the lower domestic margin by higher volumes. Inward-oriented protectionist policies are not particularly successful in exporting higher share of domestic content, except in services exports; but in this case, export volumes remain marginal.
Keywords: D57; F13; F14; F15; F23; O19; O24; 330; trade in value-added; global value chains; trade policy; input-output analysis; effective protection rate; exploratory data analysis